APPROXIMATION OF THE DISTANCE IN THE SPHERE THROUGH OF THE NUMERICAL SOLUTION OF INITIAL VALUE PROBLEM ASSOCIATED TO GEODESICS - Rubio, Franco (2016)
In this paper, we proposes an algorithm to approximate the Geodesic distance between points p and q of sphere, through the numerical solution of initial value problem associated with the system of ordinary differential equations of the geodesics; for this an appropriate direction is obtained.